Konflik Bernuansa Agama dalam Perspektif Sufisme Ibn ‘Arabî - Khadijah Khadijah (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2014)
Along the history of religions, no religion in this world teaches the follower to bring turmoil toward others. All religion thought have many differences either in terms of the way of worships and teachings principally mean for creating the perfect being (al-Insân al-Kâmil) with the good character (akhlâq al-karîmah). However, some turbulence and conflict in the name of religion sometimes happen in several areas in this country. It seems that such problems constitute an accumulative problem of Indonesia national state on the transitional era occurred in the local government. For this matter, this research is based on religious and social care-ness to elucidate and solve what is so called as “religious violence”. Principally we still have problem with how to deal with religious pluralism. As a plural and multicultural society, the majority of Indonesia people did not literally and culturally understand how to solve social conflict using religious (Islamic) approach. The question “how to deal with religious conflict and make reconciliation” is still difficult to be answered. This article aims to explore the concept of Ibn ‘Arabi’s approach for reconciliation. There are at least two questions tried to be described in this paper: (1) what is the Ibn ‘Arabi’s concept of religious approach for conflict reconciliation, and (2) what are the ideal approaches to solve religious conflict.